Astrobioethics - Chon Torres, Octavio Alfonso (2017)
Astrobiology is a discipline that is expanding its field of investigation not only in the natural sciences, but also in the social sciences. It is for this reason that the ethical aspects are progressively emphasized leading to a point where the whole field requires a specific handling. The appellation ‘astrobioethics’ is now considered as not only relevant, but also a true issue for the future of Astrobiology. Astrobioethics is the subsection within astrobiology that is accountable for studying the moral implications of, for example, bringing humans to Mars, the Planetary Protection Policy, the social responsibility of the astrobiologist to society, etc. It is in this way that the present article outlines a path for astrobioethics, as being a fertile field of study and an opportunity to trade scientific knowledge in a transdisciplinary way.